Baseline CXCL10 and CXCL13 levels are predictive biomarkers for tumor necrosis factor inhibitor therapy in patients with moderate to severe rheumatoid arthritis: a pilot, prospective study. Issue 1 (December 2016) - Han, Bobby; Kuzin, Igor; Gaughan, John; Olsen, Nancy; Bottaro, Andrea
Abstract Background TNF inhibitors have been used as a treatment for moderate to severe RA patients. However, reliable biomarkers that predict therapeutic response to TNF inhibitors are lacking. In this study, we investigated whether chemokines may represent useful biomarkers to predict the response to TNF inhibitor therapy in RA. Methods RA patients (n = 29) who were initiating adalimumab or etanercept were recruited from the rheumatology clinics at Cooper University Hospital. RA patients were evaluated at baseline and 14 weeks after TNF inhibitor therapy, and serum levels of CXCL10, CXCL13, and CCL20 were measured by ELISA. Responders (n = 16) were defined as patients who had good or moderate response at week 14 by EULAR response criteria, and nonresponders (n = 13) were defined as having no response. Results Responders had higher levels of baseline CXCL10 and CXCL13 compared to nonresponders (p = 0.03 and 0.002 respectively). There was no difference in CCL20 levels. CXCL10 and CXCL13 were highly correlated with each other, and were higher in seropositive RA patients. CXCL10 and CXCL13 levels were decreased after TNF inhibitor therapy in responders. Baseline additive levels of CXCL10 + 13 were correlated with changes in DAS score at 14 weeks after TNF inhibitor therapy (r = 0.42, p = 0.03), and ROC curve analyses for predictive ability of CXCL10 + 13 showed an AUC of 0.83. Conclusions Elevated baseline levels of CXCL10 and CXCL13 were associated with favorable response to TNF inhibitor therapy in RA. Subjects with high CXCL10 and high CXCL13 may represent a subset of RA patients whose inflammatory reactions are primarily driven by TNF.